Immediate and longer-term impacts of fetal surveillance education on workforce knowledge and cognitive skills [version 1; peer review: 2 approved] - Nathan Zoanetti; Mark Beaves; Kirsten R Palmer; Euan M Wallace (MedEdPublish, 2023)
Background: Following the development of the Royal Australian College of Obstetricians and Gynaecologists Intrapartum Fetal Surveillance Guideline in 2003, an education program was developed to support guideline implementation and clinical practice. It was intended that improved clinician knowledge, particularly of cardiotocography, would reduce rates of intrapartum fetal morbidity and mortality. The program contains a multiple-choice assessment, designed to assess fetal surveillance knowledge and the application of that knowledge. We used the results of this assessment over time to evaluate the impact of the education program on clinicians’ fetal surveillance knowledge and interpretive skills, in the immediate and longer-term. Methods: We undertook a retrospective analysis of the assessment results for all participants in the Fetal Surveillance Education Program, between 2004 and 2018. Classical Test Theory and Rasch Item Response Theory analysis were used to evaluate the statistical reliability and quality of the assessment, and the measurement invariance or stability of the assessments over time. Clinicians’ assessment scores were then reviewed by craft group and previous exposure to the program. Results: The results from 64,430, broadly similar assessments, showed that participation in the education program was associated with an immediate improvement in clinician performance in the assessment. Performance improvement was sustained for up to 18 months following participation in the program and recurrent participation was associated with progressive improvements. These trends were observed for all craft groups (consultant obstetricians, doctors in training, general practitioners, midwives, student midwives). Conclusions: These findings suggest that the Fetal Surveillance Education Program has improved clinician knowledge and the associated cognitive skills over time. The stable difficulty of the assessment tool means any improvement in clinician’s results, with ongoing exposure to the program, can be reliably assessed and demonstrated. Importantly this holds true for all craft groups involved in intrapartum care and the interpretation of cardiotocography.